2018
DOI: 10.2174/1389203719666180111150008
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Use of Peptides in Cancer Treatment

Abstract: Conventional chemotherapeutic drugs have significant limitations. For example, tumors may develop resistance, cancers may relapse after treatment, and the drugs may induce secondary malignancies in the treatment of metastatic cancer. There is still a great need for drugs that are able to destroy cancer cells selectively, that is, to effectively treat slow-growing and dormant cells without being affected by chemoresistance mechanisms. A growing number of studies indicate that peptides may be beneficial for drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 0 publications
0
38
0
Order By: Relevance
“…Peptide‐based targeted cancer therapy offers high specificity with low side effects compared with conventional chemotherapy . Several cationic and anionic linear peptides have been shown to be effective against different types of cancer cells . Despite the proven efficacy against cancer, the limited success of the linear peptides in cancer therapy is explained by their poor pharmacokinetic, low stability, and inefficient delivery .…”
Section: Introductionmentioning
confidence: 99%
“…Peptide‐based targeted cancer therapy offers high specificity with low side effects compared with conventional chemotherapy . Several cationic and anionic linear peptides have been shown to be effective against different types of cancer cells . Despite the proven efficacy against cancer, the limited success of the linear peptides in cancer therapy is explained by their poor pharmacokinetic, low stability, and inefficient delivery .…”
Section: Introductionmentioning
confidence: 99%
“…In humans, over 130 peptides have been described, and while the vast majority has been tested as potential antimicrobial drugs, AMPs have a larger impact than just direct antimicrobial effects, actively engaging with the host immune system, modulating its activity, promoting chemotaxis and cell recruitment, meddling with the inflammatory and wound healing pathways, among many different functions (Hancock et al, 2016;Mahlapuu et al, 2016;Haney et al, 2017). AMPs were also shown to have an anticarcinogenic effect, as extensively reviewed (Wang, 2014;Hancock et al, 2016;Haney et al, 2017;Yavari et al, 2018;Wang et al, 2019;Kunda, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have indicated that peptides may be beneficial for drug discovery and development. Peptides offer minimal immunogenicity, excellent tissue penetrability, low‐cost manufacturability and they are also relatively easy to modify to enhance in vivo stability and biological activity, such properties which make them ideal candidates for cancer treatment (Yavari, Mahjub, Saidijam, Raigani, & Soleimani, 2018).…”
Section: Introductionmentioning
confidence: 99%